2011
DOI: 10.1007/s11120-011-9702-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen evolution from single- and multiple-turnover light pulses: temporal kinetics of electron transport through PSII in sunflower leaves

Abstract: Oxygen evolution per single-turnover flash (STF) or multiple-turnover pulse (MTP) was measured with a zirconium O(2) analyzer from sunflower leaves at 22 °C. STF were generated by Xe arc lamp, MTP by red LED light of up to 18000 μmol quanta m(-2) s(-1). Ambient O(2) concentration was 10-30 ppm, STF and MTP were superimposed on far-red background light in order to oxidize plastoquinone (PQ) and randomize S-states. Electron (e(-)) flow was calculated as 4 times O(2) evolution. Q (A) → Q (B) electron transport wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It would be difficult to explain such a linearity on the basis of occasional overlapping of several nonlinearities having opposite direction. Rather we tend to believe that during the decay from F r to F 0 fluorescence proportionally reflected the PQH 2 level, consistently with PQH 2 being a strongly binding competitive product inhibitor for PSII [51]. Thus, we interpret our experiments showing that the kinetics of PQH 2 oxidation are of the first order with respect to PQH 2 concentration over its full redox range; with respect to O 2 the kinetics saturate with an apparent K m (O 2 ) of 60 μM (4.6%).…”
Section: Plastoquinol Oxidation By Dioxygenmentioning
confidence: 88%
See 3 more Smart Citations
“…It would be difficult to explain such a linearity on the basis of occasional overlapping of several nonlinearities having opposite direction. Rather we tend to believe that during the decay from F r to F 0 fluorescence proportionally reflected the PQH 2 level, consistently with PQH 2 being a strongly binding competitive product inhibitor for PSII [51]. Thus, we interpret our experiments showing that the kinetics of PQH 2 oxidation are of the first order with respect to PQH 2 concentration over its full redox range; with respect to O 2 the kinetics saturate with an apparent K m (O 2 ) of 60 μM (4.6%).…”
Section: Plastoquinol Oxidation By Dioxygenmentioning
confidence: 88%
“…As in the PSI cycle [58], there is a fast component in the PSII cycle that evidently is not proton-coupled, but facilitates charge recombination within PSII at high light intensities [33]. Parallel measurements revealed that the higher the light intensity, the larger became the gap between the rate of PSII charge separation as detected from Chl fluorescence and the rate of LEF through PSII as detected from O 2 evolution [34,51]. The difference was explained by charge recombination on the donor side of PSII, from excited P680* to oxidized tyrosine Z [35].…”
Section: Proton Transporting Psii Cyclementioning
confidence: 98%
See 2 more Smart Citations
“…Orange light of 630 nm that acted as PSI light when applied at very low intensity in F 0 rise experiments ( Figure 2) caused an intermediate redox state at the moderate intensity used in PQ measurements (Figure 3). These results indicate that the photosystem preferences of the wavelengths exert large effects on the redox state of the PQ pool under monochromatic light of moderate intensity, although the absorption differences between the photosystems are modest ( Figure 2); see also Canaani and Malkin (1984), Veeranjaneyulu and Leblanc (1994) Photosynthetic electron transfer reflects the state of the PQ pool A reduced PQ pool promotes high Chl a fluorescence by slowing down reoxidation of Q A (De Wijn and van Gorkom, 2001;Oja et al, 2011) and, indeed, leaves illuminated with wavelengths favoring PSII had a higher Chl a fluorescence yield than leaves illuminated with PSI wavelengths (Figure 4). Accordingly, the combined absorbance signal of the oxidized primary donor of PSI (P 700 + ) and PC (Schreiber et al, 1988) was weaker in PSII than in PSI light (Figure 4).…”
Section: Wavelength Dependence Of the Redox State Of The Pq Pool In Amentioning
confidence: 96%